2022
DOI: 10.1111/1753-6405.13296
|View full text |Cite
|
Sign up to set email alerts
|

Improving type 2 diabetes care and self‐management at the individual level by incorporating social determinants of health

Abstract: ocially disadvantaged people are more likely than those of greater affluence to develop type 2 diabetes mellitus (T2DM). 1 Disadvantaged people also encounter more challenges when managing T2DM because of their life circumstances. [1][2][3][4] Underpinning the injustice of social disadvantage are poor social determinants of health (SDoH) such as low income, suboptimal education, inadequate transport, limited healthcare access and adverse living conditions. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…16,17 Current research in other contexts have shown the importance of taking a socioecological approach to T2DM education and self-management programs. [18][19][20] The participants with a self-reported diagnosis of T2DM had elevated DBP and SBP levels, an elevated pulse pressure, and elevated triglycerides compared to the participants without a self-reported diagnosis of T2DM. These findings indicate an elevated risk for cardiac impairment and heart disease in those with T2DM, amplifying the risk of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Current research in other contexts have shown the importance of taking a socioecological approach to T2DM education and self-management programs. [18][19][20] The participants with a self-reported diagnosis of T2DM had elevated DBP and SBP levels, an elevated pulse pressure, and elevated triglycerides compared to the participants without a self-reported diagnosis of T2DM. These findings indicate an elevated risk for cardiac impairment and heart disease in those with T2DM, amplifying the risk of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Current research in other contexts have shown the importance of taking a socioecological approach to T2DM education and self-management programs. 18 20 …”
Section: Discussionmentioning
confidence: 99%